Patient understanding of diagnostic ultrasound examinations in an Australian private radiology clinic. Issue 2 (29th November 2020) - Starcevich, Amy; Lombardo, Paul; Schneider, Michal
Abstract: Purpose: To determine patient understanding and expectations of ultrasound imaging and its safety, sources of examination information and levels of examination anxiety. Methods: 1070 consecutive patients presenting to a private, regional radiology practice in New South Wales, Australia between 16 th May and 14 th June 2019, were invited to complete a survey while waiting for their non‐interventional ultrasound examination. The survey included questions on demographic characteristics, knowledge such as examination risks and safety, ultrasound expectations such as dissemination of results, sources of examination information and levels of participant anxiety. Data were analysed using Kruskal–Wallis tests (SPSS v. 25) to determine statistical associations between participant demographic factors, knowledge, anxiety level and the main source of examination information. Results: A total of 215/1070 (20%) patients voluntarily participated in the study. Most were female (74%, 159/215), with a median (range) age of 55 (18–92) years. Participant's median (range) score of ultrasound imaging knowledge was 3 (0–5) scored out of six and indicated uncertainty regarding the ultrasound procedure, result dissemination and ultrasound safety. Participants with previous personal experience had significantly higher levels of ultrasound imaging knowledge than those whose primary information source was their referring doctor (P = 0.0005) or the internet (P = 0.026). Significantly higher levels of ultrasound examination knowledge were also associated with lower self‐reported levels of anxiety (P = 0.002). Conclusion: Participants had incomplete ultrasound examination knowledge, including misconceptions regarding safety and result dissemination, some of which could be clarified by the sonographer at the beginning of the ultrasound examination.